2020
DOI: 10.1111/epi.16501
|View full text |Cite
|
Sign up to set email alerts
|

Semiologic subgroups of insulo‐opercular seizures based on connectional architecture atlas

Abstract: Objective: Insulo-opercular seizures are characterized by diverse semiology, related to the insula's multiple functional roles and extensive connectivity. We aimed to identify semiologic subgroups and correlate these with insulo-opercular subregions based on connectional architecture. Methods: We retrospectively collected a large series of 37 patients with insuloopercular seizures explored by stereoelectroencephalography (SEEG) from three epilepsy centers. A new human brain atlas (Brainnetome Atlas, BNA) based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 43 publications
(57 reference statements)
2
24
0
Order By: Relevance
“…Benbadis et al showed that unilateral blinking could be a reliable lateralizing sign after he described 38 seizures in 14 patients, with unilateral blinking ipsilateral to the lesion in 10, which led to a positive predictive value for ipsilateral ictal EEG localization of 83% [5]. Ipsilateral blinking has been found to be a frequent sign in insular seizures [11,12]. Cases reports have reported similar features using scalp EEG [8,9].…”
Section: Ictal Features According To Soz Localizationmentioning
confidence: 96%
See 2 more Smart Citations
“…Benbadis et al showed that unilateral blinking could be a reliable lateralizing sign after he described 38 seizures in 14 patients, with unilateral blinking ipsilateral to the lesion in 10, which led to a positive predictive value for ipsilateral ictal EEG localization of 83% [5]. Ipsilateral blinking has been found to be a frequent sign in insular seizures [11,12]. Cases reports have reported similar features using scalp EEG [8,9].…”
Section: Ictal Features According To Soz Localizationmentioning
confidence: 96%
“…Ictal blinking has been reported to be a frequent early sign in occipital lobe seizures [7], but has been also observed in other forms of epilepsies as temporal, frontal lobe or insular seizures [8][9][10][11][12].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation
“…64 Each patient also expressed fear because the ventral anterior insula is involved in emotional processing. 100,101 According to the anatomic-electro-clinical data of insular lobe epilepsy by Wang et al, 102 based on the Brainnetome Atlas, the semiology followed the anteroposterior "anteroventral to posterodorsal axis" distribution pattern. The semiology pattern in a group of patients with an epileptic network involving the anteroventral insular regions showed integrated gestural motor behaviors or feelings of rage or fear, whereas that in a group of patients with an epileptic network involving the posterodorsal insular regions showed non-integrated gestural motor behaviors or asymmetric tonic posture (Figure 2).…”
Section: She Of Insula Lobe Originmentioning
confidence: 99%
“…Ictal blinking has been described in epilepsy patients, most frequently with parieto-occipital and insulo-opercular seizure onsets and typically manifested bilaterally (Marchi et al 2016 ; Lagarde et al 2020 ; Peltola et al 2020 ; Wang et al 2020 ). Unilateral blinking only occurred in association with an activation of the mesial temporal lobe in a large-scaled SEEG study (Lagarde et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%